2004
DOI: 10.1074/jbc.m400009200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of Bifunctional Thymidylate Synthase-Dihydrofolate Reductase (TS-DHFR) from Cryptosporidium hominis

Abstract: This study presents a kinetic characterization of the recently crystallized bifunctional thymidylate synthasedihydrofolate reductase (TS-DHFR) enzyme from the apicomplexa parasite, Cryptosporidium hominis. Our study focuses on determination of the C. hominis TS-DHFR kinetic mechanism, substrate channeling behavior, and domain-domain communication. Unexpectedly, the unique mechanistic features of C. hominis TS-DHFR involve the highly conserved TS domain. At 45 s ؊1 , C. hominis TS activity is 10 -40-fold faster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 31 publications
6
58
0
Order By: Relevance
“…Because of the structural similarity between L. major DHFR-TS and other protozoan DHFR-TS enzymes, we hypothesized that these other enzymes may also support significant electrostatic channeling of dihydrofolate. However, despite multiple kinetic experiments investigating substrate channeling in this system, it has been found that the structurally similar DHFR-TS enzyme from C. hominis does not exhibit any measurable substrate channeling (12). This experimental result suggests that different protozoan DHFR-TS enzymes may exhibit varying efficiency of substrate channeling.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Because of the structural similarity between L. major DHFR-TS and other protozoan DHFR-TS enzymes, we hypothesized that these other enzymes may also support significant electrostatic channeling of dihydrofolate. However, despite multiple kinetic experiments investigating substrate channeling in this system, it has been found that the structurally similar DHFR-TS enzyme from C. hominis does not exhibit any measurable substrate channeling (12). This experimental result suggests that different protozoan DHFR-TS enzymes may exhibit varying efficiency of substrate channeling.…”
Section: Introductionmentioning
confidence: 90%
“…Although our main focus is on the electrostatic channeling of dihydrofolate in P. falciparum DHFR-TS, to see if this inefficient channeling observed in P. falciparum DHFR-TS is exceptional or general in the family of protozoan DHFR-TS enzymes, we include one more protozoan species, C. hominis, of the bifunctional DHFR-TS enzyme family that has been the focus of experimental kinetic studies (12), and we calculate the dihydrofolate channeling efficiency to compare the channeling efficiency between three species of protozoan DHFR-TS enzymes (P. falciparum, L. major, and C. hominis). It is known that L. major DHFR-TS exhibits substantial dihydrofolate channeling with some predictions of R80% transfer efficiency (6), whereas dihydrofolate channeling in C. hominis DHFR-TS is known to be minimal or nonexistent (12).…”
Section: Comparison Between Protozoan Dhfr-ts Enzymesmentioning
confidence: 99%
“…These residues lie at one end of the cofactor-binding site near the solvent-exposed glutamate tail of mTHF and other folate-like molecules when bound. Alanine and serine at these positions are associated with higher TS reaction rates, as observed for DHFR-TS from C. hominis relative to L. major and those of other species (Atreya & Anderson, 2004;Doan et al, 2007).…”
Section: Comparison Of Dhfr and Ts From B Bovis And Other Organismsmentioning
confidence: 75%
“…Those sequences were analyzed by multiple alignment have presented lack of similarity with each other (data not shown), with exception of species of the same genus. This, in part, could explain the absence of homology found between junctional peptides of bifunctional DHFR-TS in protozoa (Atreya and Anderson, 2004;Miles et al, 1999;Trujillo et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…TS and DHFR are enzymes that work together in successive reactions of folate synthesis pathway. These proteins exist, in some protozoans, as bifunctional enzymes, which are important in channeling the substrate between TS and DHFR active sites (Atreya and Anderson, 2004;Miles et al, 1999;Trujillo et al, 1997). These genes are neighbors in some bacterial genomes, whereas they are located millions of base pairs apart (and even in opposite DNA strands) in others.…”
Section: Introductionmentioning
confidence: 99%